Source characterisation and loads of metals and pesticides in urban wet weather discharges. Issue 6 (17th August 2016) - Becouze-Lareure, C.; Dembélé, A.; Coquery, M.; Cren-Olivé, C.; Barillon, B.; Bertrand-Krajewski, J.-L.
Abstract : Contaminants in urban wet weather discharges originate from a number of sources such as materials from wet and dry atmospheric deposition, wastewaters, urban surface erosion, traffic-related activities, in-sewer deposits, etc. In the current study, four contributions (rainwater, dry atmospheric deposition, dry weather discharge and catchment surface + possible erosion of in-sewer deposits) to the total concentrations of priority substances have been assessed at the outlet of two urban catchments (one residential catchment with a combined system and one industrial area with a separate stormwater system) for 12 storm events (six for each catchment). Mass balances were calculated for seven metals and four pesticides, as well as for total suspended solids and chemical oxygen demand. The respective contributions of dry and wet atmospheric deposition, wastewater and catchment surface differ for each pollutant type, corresponding to different land use, activities, environments and sewer systems. For most of the pollutants, the catchment surface appears to be the main contribution, with significant storm event variability, excepted for atrazine in one catchment.